Financial stability in dollarized economies - Gulde, Anne Marie; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This occasional paper addresses the challenges to prudential supervision in highly dollarized economies where central banks and supervisors may be constrained in the use of standard monetary and financial policy tools.
Includes bibliographical references (p. 27-29).
osa13/06/13
Loans
Keywords: Dollar, American; Monetary policy; Banks and banking